The United States and the Caribbean Republics, 1921-1933 - Munro, Dana Gardner, 1892-1990 (Book collections on Project MUSE., 1974)
Between 1921 and 1933, the United States moved from a policy of active intervention to a policy of noninterference in the internal political affairs of the Caribbean states. How the shift from the diplomacy of the Taft and Wilson administrations to the Good Neighbor policy of Franklin Roosevelt occurred is the subject of Dana Gardner Munro's book. The author draws on official records and on his personal experience as a member of the Latin American Division of the United States Department of State to piece together the history of the transition in diplomatic policy. Professor Munro concentrat.